Analysis of the Role of Accountants in the Development of Enterprise Resource Planning Systems in the Era of Industrial Revolution 4.0 - Panglewai, Dave Dominic; Indrijawati, Aini; Rahmawati; Grace T. Pontoh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the role of accountants in the development of ERP systems in the 4.0 era. Accountant roles as strategist, ERP expert, IT expert and communicator. This study uses qualitative methods with data collection techniques, namely interviews. Data validation was checked using the triangulation method. The research results show that (1) the role of the accountant as a strategist functions to review the company's system and then develop a strategy for the development of the company's system; (2) the accountant's role as an ERP expert serves as a monitor that oversees and controls the company's systems; (3) the role of the accountant as an IT expert serves to provide accounting data information in the company's system; (4) the role of accountants as communicators does not have much effect because they have been replaced by artificial intelligence functions in company system applications